2005
DOI: 10.1007/s11062-005-0044-0
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry of Motor Behavior of the Goldfish in a Narrow Channel

Abstract: We studied swimming of goldfish fries about 3 cm long in a narrow channel by calculating the numbers of spontaneous turns on different sides. The ratio of fishes preferring to turn to the right vs to the left was 1.5: 1.0, respectively; two-thirds of the fishes demonstrated an ambilateral behavior. Experiments with compulsory 10-min-long rotation of the fishes (clockwise around the longitudinal body axis for fishes preferring right-side turns and anticlockwise for fishes preferring left-side turns) showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…Applications of the neurotransmitters were always performed at the right side of the fish's head, and the preferred side of turning is determined by the functioning of the contralateral MN [20]; this is why we used in the morphological part of the study mostly fishes preferably turning to the left, with domination of the right MN. The functional state of MNs in these experiments was estimated by separate calculation of rightward and leftward turnings in a straight channel and characterized by the motor asymmetry coefficient (MAC), i.e., by the ratio of the number of turnings toward the preferred side to the number of turnings toward both sides [21,22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Applications of the neurotransmitters were always performed at the right side of the fish's head, and the preferred side of turning is determined by the functioning of the contralateral MN [20]; this is why we used in the morphological part of the study mostly fishes preferably turning to the left, with domination of the right MN. The functional state of MNs in these experiments was estimated by separate calculation of rightward and leftward turnings in a straight channel and characterized by the motor asymmetry coefficient (MAC), i.e., by the ratio of the number of turnings toward the preferred side to the number of turnings toward both sides [21,22].…”
Section: Methodsmentioning
confidence: 99%
“…When studying the effects of applications of neurotransmitters, we combined these applications in a few cases with natural long-lasting stimulation of MNs (bilateral stimulation for estimation of the systemic function of both neurons and unilateral one for estimation of the function of an individual neuron) [21]. Sensory rotational stimulation was fulfilled by putting fishes into special drums rotated simultaneously in two planes (bilateral stimulation) or rotated in one plane around the longitudinal axis of the fish's body (unilateral stimulation) [22].…”
Section: Methodsmentioning
confidence: 99%
“…Before the beginning of the experiments, all fishes were divided into two groups, dextrals and sinistrals, according to their individually expressed preference of the side of turning manifested in the course of locomotion (i.e., motor asymmetry). The phenotypic motor asymmetry was estimated in a narrow straight chamber using the technique described earlier [7] and quantitatively characterized by calculation of the motor asymmetry coefficient (MAC), i.e., ratio of the number of full (90 deg or greater) turnings toward the preferred side and the total number of turnings toward both sides performed within a 5-min-long test period [11]. The level of integral functional activity of MNs of the fishes was estimated according to the total number of turnings realized within a 10-min-long interval [7].…”
Section: Methodsmentioning
confidence: 99%
“…Individual levels of receptivity of each dendrite and certain MN as a whole observed in each definite time moment also influence the selection of the turning direction. They are, to a considerable extent, determined, on the one hand, by the morphofunctional asymmetry of MNs that is manifested in behavior as the motor asymmetry of the fish [7,8] and, on the other hand, by variations of this asymmetry depending on the preceding loading on one afferent input or another. It was found that experimental adequate stimulation or unilateral elimination of one input selectively influences the structure and function of the individual MN; this leads to a change in the inborn motor asymmetry of the fish [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation